Optimization of xylitol production from xylose by a novel arabitol limited co-producing Barnettozyma populi NRRL Y-12728. Issue 8 (1st September 2021) - Saha, Badal C.; Kennedy, Gregory J.
Abstract: Xylitol is a widely marketed sweetener with good functionality and health-promoting properties. It can be synthetized by many yeast species in a one-step reduction of xylose. Arabinose is a common contaminant found in xylose and there is ongoing interest in finding biocatalysts that selectively produce xyltiol. From a screen of 99 yeasts, Barnettozyma populi Y-12728 was found to selectively produce xylitol from both mixed sugars and corn stover hemicellulosic hydrolysate. Here, fermentation conditions for xylitol production from xylose by B. populi were optimized. The medium for xylitol production was optimized through response surface methodology. The yeast produced 31.2 ± 0.4 g xylitol from xylose (50 g L −1 ) in 62 h using the optimized medium. The optimal pH for xylitol production was 6.0. Glucose (10 g L −1 ), acetic acid (6.0 g L −1 ), HMF (4 mM) and ethanol (2.0 g L −1 ) inhibited the xylitol production. The glucose inhibition was entirely mitigated by using a 2-stage aeration strategy, indicating that the yeast was inhibited by ethanol produced from glucose under low aeration. This culture strategy will greatly benefit xylitol production from hemicellulosic hydrolysates, which often contain glucose. This is the first report on optimization of xylitol production by a Barnettozyma species.